Case Report: Coronaro-bronchial fistula vascularizing a squamous cell lung cancer - Ntshaykolo, Chloe; Fave, Thomas; Benic, Clement; Boizet, Antoine; Geier, Margaux; Nicol, Pierre-Philippe; Descourt, Renaud (Frontiers in Cardiovascular Medicine, 2023)
Coronary fistulas are rare, described for the first-time postmortem by Krauss in 1865. Usually asymptomatic, they can be the result of congenital or acquired malformations. We present the singular case of a 65-year-old patient treated for a squamous cell lung cancer with chemo-immunotherapy and presenting with chest pain angina like. Coronary angiography showed a coronarobronchial fistula that arises from a branch of the right coronary artery and connects with the lung cancer.